Career guidance in South Africa as a social justice travesty - Sefotho, Maximus Monaheng (2017)
This article covers the subject of career guidance in South Africa. The education of the black people is contextualized in social injustices from the time of the system of apartheid to the present day. The question this research answered was: How do the experiences of career fairs for students living in poor communities contribute to innovative models for provision of socially just career guidance? The methodology was qualitative-phenomenological with the auto-ethnographic case design. The apartheid system was designed to hold back black people. The architect of that system once declared a political and systematized exclusion of the black child through the Bantu education system for the black people who were neglected. In this article I show how career guidance was a system used by the government to marginalize the black child. Even today, psychology is still used as a tool to subjugate black students. A great majority of them do not access educational programs in disciplines such as psychology with a consequence of a smaller number of black lecturers in the field of career guidance. This journey of social injustice lies at the center of the educational system to this day, and as a measure towards decolonization and inclusion, the status quo has to change because it is a social justice travesty.